Veterans' Satisfaction analysis of Disability rating commission - E. Modirian; A.H. Eskandari (Afarand Scholarly Publishing Institute, 2010)
Introduction: Medical disability rating Commission is the only way through Iranian Veterans and War Victims' Organization and allocation of all facilities is related to its permission. In this study we were to assess veterans' satisfaction from this process. Materials and Methods: All the veterans who had attended for the commission session were asked to fulfill a questionnaire covering different aspects of the evaluation process and all the data were collected and analyzed by using SPSS 15 software Results: Most of the veterans were from Geylan, Khorasan and East Azarbayejan provinces 9.8%, 8.2% and 7.4%, respectively. Their mean age was 39.9±6.6 (Range: 12-83 y/o). At the time of study, 44.3% of the veterans were unemployed and mean disability percent of them was 25.8±8.6 (Range: 5-70%) and five percent of the subjects were injured after the ceasefire in 1987. According to their opinion, 87.8% of the subjects reported that local officials had very good or excellent greetings and 87.7% reported that they had been visited according to the schedule. 8.4% reported that they had to wait a long time to be visited and 6.4% were unsatisfied from physical environment of the programs. Seventy two percent of the subjects were satisfied from attention and consideration of the specialists. Discussion: As Iranian Veterans and War Victims' Organization is dedicated to afford veterans' needs, the officials should use all their authority to enhance their abilities to cope with the society.